Burry, Emma. Sunshine Park Killer Urban Legend. - Jarvis, Dale Gilbert, 1971- (2011)
Recording of an urban legend told by Emma Burry, a Grade 9 student at Leary's Brook Junior High. Recorded in the Newman Wine Vaults Provincial Historic Site as part of the Young Folklorists Program run by the Heritage Foundation of Newfoundland and Labrador in May, 2011. Emma writes, "I heard this story from one of the counsellors at the summer camp I went to one year. It takes place at Sunshine Park in the summertime, approximately 20 years ago. It has to do with the actual camp I went to and one of the events that they do every year."